Inhomogeneous-strain-induced magnetic vortex cluster in one-dimensional manganite wire - Malik, Iftikhar Ahmed; Huang, Houbing; Wang, Yu; Wang, Xueyun; Xiao, Cui; Sun, Yuanwei; Ullah, Rizwan; Zhang, Yuelin; Wang, Jing; Malik, Muhammad Abdullah; Ahmed, Irfan; Xiong, Changmin; et al. (2020)
Mixed-valance manganites with strong electron correlation exhibit strong potential for spintronics, where emergent magnetic behaviors, such as propagation of high-frequency spin waves and giant topological Hall Effects can be driven by their mesoscale spin textures. Here, we create magnetic vortex clusters with flux closure spin configurations in single-crystal La0.67Sr0.33MnO3 wire. A distinctive transformation from out-of-plane domains to a vortex state is directly visualized using magnetic force microscopy at 4 K in wires when the width is below 1.0 μm. The phase-field modeling indicates that the inhomogeneous strain, accompanying with shape anisotropy, plays a key role for stabilizing the flux-closure spin structure. This work offers a new perspective for understanding and manipulating the non-trivial spin textures in strongly correlated systems.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Cryo-Temperature MFM; Epitaxial thin films; Inhomogeneous strain; Magnetic vortex cluster; One-dimensional manganites